Changes in typical Acrisol under vineyard in southern Brazil (Research, Society and Development, 2021)
This work aimed to evaluate the mineralogical evolution and alterations caused in the soil and clay fraction after 15 years of cultivation with vines. Sampling was carried out on horizons A2 and Bt1 (up to 60 cm deep) of an Acrisol (WRB/FAO), for physical, chemical and mineralogical analyzes. The areas of this study are composed of a commercial vineyard managed for 4, 9 and 16 years with the cultivar Pinot noir (Vitis Vinifera), grafted in 1103 Paulsen, and an area under native field, located close to the vineyard to be used with reference. There was a change in soil fertility, at all depths sampled and after 4 years of planting. The predominant clay in the soil was kaolinite (Ct), containing mica (Mc), potassium feldspar (Ft) and quartz (Qz). In general, the vineyard showed changes in the chemical attributes of the soil over the years, with greater emphasis on the areas managed for 9 and 16 years, where the soil suffered a greater supply of fertilizers and agricultural corrective materials. The results obtained showed that in the vineyard cultivated 4 years ago there was evidence of Ilitization, resulting from intense potassium fertilization in the first years of cultivation, which promoted the new formation of Ilitas and inter-ratified clay minerals.